Microbial assessment of utensil and worktop surfaces at university food court / Razi Ikhwan Md Rashid ... [et al.] - Sabaruddin, Nurul Shuhada; Shafie, Farah Ayuni; Masngut, Mohd Izwan; Md Rashid, Razi Ikhwan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The contaminated utensils and worktop surfaces are known as one of the causes of food contamination. This study was conducted to identify the presence of Escherichia coli and Staphylococcus aureus on the utensils and worktop surfaces, and to identify the hygiene level in the premises and also to determine the relationship between food premise rating and the bacteria count. Environmental swab of utensils and worktop surface was carried according to ISO 18593:2004. 126 samples of swab from seven type of utensils from six food premises was collected. For the food premise rating, standard form by Ministry of Health Malaysia was used. The average numbers of Escherichia coli colonies ranged from 2.0 - 269.3 (cfu/ml). For the Staphylococcus aureus the average numbers of colonies are ranged from 1.0 - 186 cfu/ml. All the result of Staphylococcus aureus showed the positive result. The hygiene level of the premise ranged from 53% to 86%. The highest level was recorded in the premise that has 86% of evaluation marks. However there is no significant difference in mean of bacteria count in clean premises and less clean premises.